Muslim Minority in Manila: Ethnographical Studies of Minority Expression on the Archipelago - Susilo, Daniel; Sugihartati, Rahma; Santos, Roberto Rudolf T. (Al-Jami'ah: Journal of Islamic Studies, 2023)
This article describes the spiritual experience of being a Muslim and minority in Manila, the capital of Asia’s most populous Catholic country, the Philippines. This research used an ethnography approach to understand how Muslims in Manila negotiate their identity as Muslims as well as Filipinos who live in Barangay as a minority and face bad sentiment, especially after the Battle of Marawi and the Maguindanao Massacre. This research found that even when facing negative stigma on most of the national media coverage after the Battle of Marawi and the Maguindanao Massacre, Muslims in Manila feel that they are free to express their identity as Muslims, as Anak Bansa, and as Filipinos with their limitations.[Artikel ini menggambarkan pengalaman spiritual Muslim minoritas di Manila, Filipina, negara dengan umat Katolik terbesar di Asia. Penelitian ini menggunakan pendekatan etnografi untuk melihat bagaimana Muslim di Manila menegosiasikan identitasnya sebagai orang Islam sekaligus sebagai orang Filipina yang hidup di Barangay sebagai minoritas, terutama dalam menghadapi sentimen buruk pasca Perang Marawi dan Pembantaian Maguindanao. Penelitian ini menemukan bahwa meskipun menghadapi stigma buruk dalam hampir semua media nasional pasca Perang Marawi dan Pembantaian Maguindanao, orang Islam di Manila tetap merasa bebas mengekspresikan identitas mereka dengan segala keterbatasannya sebagai Muslim sekaligus sebagai Anak Bangsa dan orang Filipina.]